Association between participation in the free nutritious meal program and nutritional status among junior high school students - Reyva Putri Bani; Tessa Sjahriani; Sandhy Arya Pratama; Laurentia Konadi Miharja (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Adolescents are a demographic that may face nutritional challenges, which can impact their growth, health, focus, and academic success. Based on the 2023 Indonesian Health Survey, 7.6% of adolescents aged 13–15 years were thin or severely thin, 12.1% were overweight, and 4.1% were obese. The Free Nutritious Food Program or Makan Bergizi Gratis (MBG) aims to address the nutritional needs of school-age children; however, variations in students' consumption patterns may influence the outcomes. Purpose: To determine the association between Free Nutritious Meal Program (MBG) consumption and the nutritional status of junior high school students. Method: This study employs an observational analytical design utilizing a cross-sectional approach. The research sample included 100 students who were chosen through a simple random sampling method. Data were collected through structured questionnaires, measurement of weight and height, and determination of BMI/U based on z-score. Results: The analysis of the data was conducted using Fisher’s Exact test. The research findings indicated that 77 students, representing 77.0%, exhibited good nutritional status. According to MBG consumption data, 60 students, representing 60.0%, were categorized as frequent consumers, while 40 students, or 40.0%, were classified as infrequent consumers. A total of 44 students (73.3%) in the frequent consumption group and 33 students (82.5%) in the infrequent consumption group exhibited good nutritional status. The Fisher’s Exact test results indicate a significant relationship between MBG consumption and students' nutritional status, with a p value = 0.011. Conclusion: MBG consumption frequency was significantly associated with nutritional status; however, frequent consumption was not consistently associated with a higher proportion of normal nutritional status. Longitudinal studies accounting for total dietary intake and physical activity are required.